1997
DOI: 10.1136/bmj.315.7103.279
|View full text |Cite
|
Sign up to set email alerts
|

Prospective population based survey of outcome of pregnancy in diabetic women: results of the Northern Diabetic Pregnancy Audit, 1994

Abstract: Objective: To determine whether the St Vincent declaration (1989) target of diabetic pregnancy outcome approximating non-diabetic pregnancy outcome is near to being achieved. Design: Prospective collection of population based information on pregnancies in women with diabetes from all participating hospitals. Setting: District general and teaching hospitals of the former Northern region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

21
164
3
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(190 citation statements)
references
References 10 publications
21
164
3
2
Order By: Relevance
“…The incidence of congenital malformation in type 1 diabetic pregnancy is estimated to be 4.2% to 9.4% compared with approximately 1% in the general population [1][2][3]. Although a planned pregnancy with optimal blood glucose control and folic acid supplements at the time of conception reduces the risk of congenital malformations, a recent prospective study showed that the incidence of congenital malformations is still elevated in women with type 1 diabetes [4].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of congenital malformation in type 1 diabetic pregnancy is estimated to be 4.2% to 9.4% compared with approximately 1% in the general population [1][2][3]. Although a planned pregnancy with optimal blood glucose control and folic acid supplements at the time of conception reduces the risk of congenital malformations, a recent prospective study showed that the incidence of congenital malformations is still elevated in women with type 1 diabetes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Macrosomia is a frequent complication in pregnancies of women with type 1 diabetes [1][2][3][4]. Macrosomia may lead to short-term complications such as increased rates of Caesarean section, shoulder dystocia and neonatal hypoglycaemia [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally agreed that the rate of macrosomia decreases when diabetic control in pregnant women with type 1 diabetes is tightened [13,14]. However, even in patients with near-normal HbA 1 c levels, macrosomia rates remain high [2,4,5]. Several studies on the relationship between HbA 1 c levels and birthweight have been published [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, congenital malformations, which occur within the first 8 weeks of pregnancy, have been particularly difficult to avoid. The frequency of congenital malformations in the offspring of diabetic mothers is estimated to be 6 -13%, a two-to fivefold increase over that in the nondiabetic population (3)(4)(5)(6)(7). The malformations associated with diabetic pregnancy affect many major organs, including the central nervous system, heart, skeleton, kidney, gastrointestinal system, and genitalia (5,6).…”
mentioning
confidence: 99%